Real-World Effectiveness of Mineralocorticoid Receptor Antagonists in Primary Aldosteronism - Tezuka, Yuta; Turcu, Adina F. (Frontiers in Endocrinology, 2021)
Background: Primary aldosteronism (PA) is associated with high cardiovascular and renal morbidity and mortality. Reversal of renin suppression by mineralocorticoid receptor antagonists (MRAs) can prevent cardiovascular events. How often such target renin levels are achieved in clinical practice has not been rigorously studied. Methods: We conducted a retrospective cohort study of all patients with PA and other low renin hypertension (LRH) treated with MRAs in an academic outpatient practice over 20 years, to assess the rates of target renin achievement. Results: Of 30,777 patients with hypertension treated with MRAs, only 7.3% were evaluated for PA. 163 patients (123 with PA) had renin followed after MRA initiation. After a median follow-up of 124 [interquartile range, 65-335] days, 70 patients (43%) no longer had renin suppression at the last visit. The proportion of those who achieved target renin was higher in LRH than in PA (53% vs. 40%). Lower baseline serum potassium, lower MRA doses, and beta-blocker use were independently associated with lower odds of achieving target renin in PA, while male sex was associated with target renin in LRH. Overall, 50 patients (30.7%) had 55 adverse events, all from spironolactone, and 26 patients (52%) were switched to eplerenone or had a spironolactone dose reduction. Conclusion: Despite evidence that reversal of renin suppression confers cardiorenal protection in patients with PA and LRH, renin targets are followed in very few and are achieved in under half of such patients seen in an academic setting, with possibly even lower rates in community practices.